Hubungan Antara Identitas Sosial dengan Perilaku Prososial pada Aktivis Komunitas Info Cegatan Jogja (ICJ) - Antonius Indra Setiawan; Aditya Nanda Priyatama; Moh Abdul Hakim (UNS Press, 2022)
Abstract. Helping behavior has a positive impact on other people or society in general. Helping behavior is also referred to as prosocial behavior, which is a voluntary and intentional behavior that has positive consequences for the welfare of another person or group. Social identity factors can influence prosocial behavior in individuals in a community. The purpose of this study was to determine the relationship between social identity and prosocial behavior in the Info Cegatan Jogja (ICJ) community activists. The population in this study were members of the Info Cegatan Jogja (ICJ) community. Sampling using a simple random sample method with a total sample of 64 people. This study uses two psychological scales, namely the social behavior scale and the social identity scale. Hypotheses were tested using regression analysis. This study shows a positive and significant relationship between social identity and prosocial behavior on Info Cegatan Jogja (ICJ) activists. (p < 0.05; r = 0.719). The R2 value of 0.517 indicates that 51.7% of prosocial behavior in the Info Cegatan Jogja community activists is influenced by social identity.